2018
DOI: 10.1016/j.jff.2018.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooking methods and intestinal conditions on lipolysis, proteolysis and xanthophylls bioaccessibility of eggs

Abstract: Digestibility of macro and micronutrients depends on the ingested food as well as on gastrointestinal conditions, being those suboptimal in exocrine pancreatic insufficiency (EPI) patients. Under this scenario, oral enzyme supplementation improves enzymatic hydrolysis of nutrients. In this study, a static in vitro model was used to assess lipids and protein digestibility as well as lutein and zeaxanthin bioaccessibility of eggs cooked differently and submitted to different intestinal conditions. Boiled, poache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 52 publications
3
34
0
Order By: Relevance
“…The 95% CI represent the extent to which the pH 7 and bile 10 mM conditions produce an increase in the total FFA. This is in accordance to previous studies conducted by our group (Asensio-Grau et al 2018 Focusing on the results when considering the food products and their type of matrix, more concrete patterns could be depicted (Table 4). Digestions conducted at intestinal pH 7, revealed that in the protein fibre matrices the higher concentration of bile salts led to a significant increase in total FFA release of up to 300 mg / g fat, while this effect of bile concentration showed a lower increase in the unstructured matrices (50 mg/ g fat, except for luncheon ham whose increase was higher).…”
Section: Effect Of the Intestinal Conditions On Matrix Degradation Ansupporting
confidence: 91%
“…The 95% CI represent the extent to which the pH 7 and bile 10 mM conditions produce an increase in the total FFA. This is in accordance to previous studies conducted by our group (Asensio-Grau et al 2018 Focusing on the results when considering the food products and their type of matrix, more concrete patterns could be depicted (Table 4). Digestions conducted at intestinal pH 7, revealed that in the protein fibre matrices the higher concentration of bile salts led to a significant increase in total FFA release of up to 300 mg / g fat, while this effect of bile concentration showed a lower increase in the unstructured matrices (50 mg/ g fat, except for luncheon ham whose increase was higher).…”
Section: Effect Of the Intestinal Conditions On Matrix Degradation Ansupporting
confidence: 91%
“…Depending on the type of protein, denaturation has proved to have different effects against digestion. For example, Asensio-Grau et al [16] found that long exposure to high temperatures in eggs (boiling) leads to lower proteolysis than shorter cooking times (poached). In plant proteins, different species have shown different behaviours towards proteolysis, and, what is more, different digestibility patterns when exposed to pepsin (gastric stage) or trypsin (intestinal stage) [47,49].…”
Section: Discussionmentioning
confidence: 99%
“…Chia seeds and derivatives were subjected to in vitro digestion. Experiments were conducted following the static in vitro digestion model that allows for simulating both standard and altered intestinal conditions [16] concretely in terms of duodenal pH and bile salts concentration [11].…”
Section: In Vitro Digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eggs are also considered a high-quality protein source by most standards. According to the Digestible Indispensable Amino Acid Score (5) , whole egg (WE) is comparable to other high-quality protein sources that often accompany RT programmes, such as whey, casein and soy protein (6)(7)(8)(9) . In addition, WE has a nitrogen protein utilisation evaluation of 98 %, which is comparable to whey and casein.…”
mentioning
confidence: 99%